Modelling the hydrology of watershed by using HEC-HMS - Makkena Jyothi (Department of Irrigation and Drainage Engineering, Kelappaji College of Agricultural Engineering and Technology, 2016)
A hydrological model is a commonly used tool to estimate the hydrological response of a watershed to precipitation. Hydrologic Modeling System (HEC-HMS) is a physically based semi-distributed hydrologic modelling software developed by the Hydrologic Engineering Center (HEC) of the U.S. Army Corps of Engineers. It is designed to simulate the complete hydrologic processes of dendritic watershed systems under various widely varying geographic conditions. HEC-HMS is widely used and includes both traditional hydrologic analysis procedures such as event infiltration, unit hydrographs, and hydrologic routing as well as continuous simulation procedures including evapotranspiration, snowmelt, and soil moisture accounting. It can be used in conjunction with other software for studies of water availability, urban drainage, flow forecasting, future urbanization impact, reservoir spillway design, flood damage reduction, floodplain regulation, and systems operation. In the present study, Hydrologic Modeling System (HEC-HMS) is calibrated and validated for Thuthapuzha sub basin of Bharathapuzha river basin in Kerala. The input data required for the model like precipitation, meteorological parameters, river discharge, soil characteristics, land use characteristics and topographical characteristics of the study area were collected from various agencies like Central Water Commission (CWC), Kerala State Land Use Board (KSLUB), RARS Pattambi and the Bhuvan geo-data portal of National Remote Sensing Centre (NRSC). The model performance of the calibrated HEC-HMS model for Thuthapuzha watershed was evaluated using the statistics -Nash Sutcliffe- model efficiency criterion, coefficient of determination and simulated time to peak. The analysis showed that CN, and lag time are the most sensitive parameters for the simulation of stream flow. The Nash-Sutcliffe model efficiency (E) was (0.77-0.8) and (0.86-0.88) and the coefficient of determination was (0.82- 0.91) and (0.91-0.93) before and after the calibration respectively, indicating the good performance of the model.